Perforating scleral vessels adjacent to myopic choroidal neovascularization achieved a poor outcome after intravitreal anti-VEGF therapy - Yao, Wangjing; Xu, Jiawen; She, Xiangjun; Yu, Jiangxin; Liang, Zhi; Ye, Xin; Tao, Jiwei; Wu, Sulan; Mao, Jianbo; Chen, Yiqi; Zhang, Yun; Shen, Lijun (Frontiers in Medicine, 2022)
Background This study aimed to summarize the features of perforating scleral vessels (PSVs) in patients with myopic choroidal neovascularization (CNV) (mCNV) using optical coherence tomography angiography (OCTA) and to identify the associations with the response after intravitreal anti-vascular endothelial growth factor (anti-VEGF) therapy. Methods A consecutive series of naïve patients who had mCNV and received intravitreal anti-VEGF therapy with a follow-up duration of 12 months or more were enrolled. The prevalence, location, and branches of PSVs were analyzed. Projection-resolved OCTA (PR-OCTA) was used to analyze the neovascular signals between CNV and PSVs. Best corrected visual acuity (BCVA) and central macular thickness (CMT) were measured. The proportion of CMT change relative to baseline was used to assess therapeutic response. Results A total of 44 eyes from 42 patients with mCNV were enrolled. PSVs were identified in 41 out of 44 eyes. Branches were identified in the PSVs of 24 eyes (57.14%), and 20 eyes did not have PSV branches (47.62%). In eight eyes (18.18%), PSVs were adjacent to mCNV, and in 36 eyes (81.82%), PSVs were not adjacent to mCNV. After anti-VEGF therapy for mCNV, BCVA increased (F = 6.119, p < 0.001) and CMT decreased (F = 7.664, p < 0.001). In the eyes where PSVs were adjacent to mCNV, BCVA improvements (F = 7.649, p = 0.009) were poor, and changes in CMT were small. Conclusion The eyes with PSVs adjacent to mCNV showed poor therapeutic responses after intravitreal anti-VEGF therapy.